Umarli nie zdradzaja - Driscoll, Peter, 1942-; Driscoll, Peter, 1942- (Warszawa : Krajowa Agencja Wydawnicza, 1988)
Polish translation of the author's "In Connection with Kilshaw", a political novel set in Ireland.
Translation of: In connection with Kilshaw.